School-Based Management in British schools and the Possibility of Benefiting from it in Saudi Arabian Public schools - A comparative study - Jannadi, Reem Ibrahim; Haweel, Enas Ibrahim (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to identify the experience of self-management in British schools and the possibility of benefiting from it in applying self-management to schools in the Kingdom of Saudi Arabia in the light of influencing factors. The researcher used the comparative approach with its descriptive and analytical approach, where the study steps proceeded according to the four-step approach of George Perday, which are: description, interpretation, classification, comparison. The research consists of an introduction, four topics and a conclusion. The first topic includes a descriptive study of the two countries, the second topic includes the educational system in the two countries in a comparative framework, and the third topic includes aspects of benefiting from the British experience. Then a conclusion that includes a summary of the most important results and recommendations of the study and its suggestions The research reached a set of results, the most important of which are: School management in England is based on the principle of local management of schools, which depends on financial delegation and granting schools the power to select and appoint working personnel, and enjoy independence and flexibility in decision-making. England relied on the application of the school’s self-management approach on the principle (participation) in decision-making by all parties concerned with the educational process, and the application of self-management for schools in the Kingdom was limited, although the Ministry of Education in the Kingdom of Saudi Arabia has granted a number of its powers to education departments, it is still closer to centralization than to decentralization, so it has become urgent to move towards decentralization by adopting an approach Self-management in public education schools to move them from the prevailing traditional style and develop them in line with s with the requirements of the current era. Based on the results, the researcher presented a number of recommendations to activate self-management in Saudi schools, including: the need to reconsider educational administrative systems in line with the spirit of the age and the requirements of the future and the Kingdom’s vision 2030, and granting local councils wide powers in educational decision-making, which makes school administration An independent entity where each school draws up its own plan and programs.
Keywords: self-management; The experience of British schools; the benefit of Saudi schools